THE METHOD OF BUILDING OF BEHAVIOR MODEL OF NON-MARKOV COMPLEX SYSTEMS AS A GRAPH OF STATES AND TRANSITIONS - Volochiy, Bohdan Y.; Ozirkovskyy, Leonid D.; Kulyk, Ihor W. (International Journal of Computing, 2014)
The goal of the paper is the construction of behavior models of discrete-continuous stochastic systems of non-Markov type by the method of Erlang’s phases. The improved method of formalized construction of behavior models as a graph of states and transitions is developed. Since this method is a part of technology modeling discrete-continuous stochastic systems, now the process of construction of behavior systems of non-Markov type is automated.